The Influence of Neurotransmitters on Cryptocurrency Investment Decision-Making : The Mediating Role of Risk Tolerance and Moderating Role of Investment Experience - Gautam, Shubhangi; Kumar, Pardeep; Dahiya, Preeti (Indian Journal of Finance, 2024)
Purpose : The current study examined the influence of neurotransmitters on cryptocurrency investment choices. Moreover, the research assessed the mediator risk tolerance (RT) and moderator investment experience on the connection between neurotransmitters and investment choices. Research Design/Methodology : The analysis of the data involved 504 responses from individuals in Indiaâ€™s Western and Northern regions who either invested in cryptocurrencies or had knowledge of such investments. The proposed theoretical model of cryptocurrency investment choices was examined in the study using â€œvariance-based partial least square structural equation modelingâ€ (PLS-SEM). Findings : The outcomes of this research specified that neurotransmitters play a substantial role in cryptocurrency investment choices, and they had a substantial impact on making investment choices. It was also noted that a significant moderator between neurotransmitters and Bitcoin investment decisions is RT. However, it was determined that investment experience had no moderating effect. Practical Implications : This study revealed that, in order to make better-informed investment decisions, businesses, governments, and investors should consider the impact of neurotransmitters. Value/Originality : The study was innovative since it is one of the first to examine how neurotransmitters, together with mediator RT and moderator investment experience, affected Bitcoin investment decisions. Additionally, the conceptual framework could be very helpful to cryptocurrency portfolio managers and investors in understanding how the brain functions during the decision-making process. They would then be better equipped to allocate their assets with knowledge and efficiency.